2018
DOI: 10.1016/j.enpol.2018.05.055
|View full text |Cite
|
Sign up to set email alerts
|

Leveraging material efficiency as an energy and climate instrument for heavy industries in the EU

Abstract: Material efficiency is indispensable to reaching agreed targets for industry's energy and carbon emissions. Yet, in the EU, the energy-and emissions-saving potentials of this strategy continue to be framed as secondary outcomes of resource-related policies. Understanding why material efficiency has been overlooked as an energy/climate solution is a prerequisite for proposing ways of changing its framing, but existing studies have failed to do so. This paper fills this gap by triangulating interviews, policy do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…Energy is an important source for running the machines and processing raw materials. In some empirical studies, material efficiency was found to have a direct proportional relationship with energy consumption and the emission of CO 2 [34,48]. In our study, some E&E companies also confirmed this view whereby if the raw material intake is reduced, the processing time could be reduced; thus, the usage of energy will decrease.…”
Section: Reduce Energy Usagesupporting
confidence: 82%
See 3 more Smart Citations
“…Energy is an important source for running the machines and processing raw materials. In some empirical studies, material efficiency was found to have a direct proportional relationship with energy consumption and the emission of CO 2 [34,48]. In our study, some E&E companies also confirmed this view whereby if the raw material intake is reduced, the processing time could be reduced; thus, the usage of energy will decrease.…”
Section: Reduce Energy Usagesupporting
confidence: 82%
“…For example, environmentally friendly products have become a trend, especially in European countries. To fulfill these market needs, manufacturers are required to practice various environmental strategies, including material efficiency [13], green packaging [32,45], consuming less energy [33,46], lightweight product design [25,47], and less CO 2 emissions [33,34,48]. Furthermore, manufacturers need to clearly understand the differences in the product requirements in various regions.…”
Section: Market Requirementsmentioning
confidence: 99%
See 2 more Smart Citations
“…More recently, Materials Economics estimated EU-level GHG emissions reductions associated with ME policies, but did so using independent models for each industrial sector, thereby lacking important economywide perspectives [12]. As a recent review found that current policies are insufficient to tap the significant mitigation potential of ME [215], improved IAM capabilities for robust, policy-relevant assessment of ME strategies should be a critical priority. Emerging work on a country level may offer indications for how the effect of ME can be modeled [216,217].…”
Section: Me In Integrated Policy Studiesmentioning
confidence: 99%